Built for growth : how builder personality shapes your business, your team, and your ability to win - Kuenne, Chris; Danner, John (Boston, Massachusetts : Harvard Business Review Press, 2017)
Many factors shape the success or failure of a new business, whether it's a stand-alone start-up or a new venture inside a larger corporation. But the most important and least understood of these factors is the personality of the builder--the founder or leader's particular combination of beliefs and preferences that drives his or her motivation, decision making, and leadership style. And it's the one factor you, as a business builder yourself, can directly control. This book decodes the interplay between builder personality and new business success or failure. Using a patented analytic methodology, authors Chris Kuenne and John Danner discovered four distinct types of highly successful "business builder" personalities--the Driver, the Explorer, the Crusader, and the Captain--each displaying special gifts and predictable gaps or shortcomings in growing their companies and new ventures. Built for Growth blends exclusive research findings, personal interviews, and experienced analysis to illustrate how each type handles the five dynamic challenges of building businesses of lasting value: converting an idea into reality, recruiting inspired talent, transforming buyers into partners, aligning financial and other supporters, and scaling the business. With vivid stories and practical tools, this book gives you unprecedented insight into the personalities of each Builder Type and how you can use that insight to assess yourself and others and improve your odds of success. Built for Growth is the ultimate guide for how to play to your strengths, complement and compensate for your gaps, and build successful businesses--from start-up to scale-up.--
Includes bibliographical references and index.
Keywords: Businesspeople -- Psychology; Success in business; Industrial management